Does Sex Modify the Effect of Endovascular Treatment for Ischemic Stroke?: A Subgroup Analysis of 7 Randomized Trials. Issue 9 (September 2019) - Chalos, Vicky; de Ridder, Inger R.; Lingsma, Hester F.; Brown, Scott; van Oostenbrugge, Robert J.; Goyal, Mayank; Campbell, Bruce C.V.; Muir, Keith W.; Guillemin, Francis; Bracard, Serge; White, Philip; Dávalos, Antoni; et al.
Abstract : Background and Purpose—: Previous studies have reported less favorable outcome and less effect of endovascular treatment (EVT) after ischemic stroke in women than in men. Our aim was to study the influence of sex on outcome and on the effect of EVT for ischemic stroke in recent randomized trials on EVT. Methods—: We used data from 7 randomized controlled trials on EVT within the HERMES collaboration. The primary outcome was 90-day functional outcome (modified Rankin Scale). We compared baseline characteristics and outcomes between men and women. With ordinal logistic regression, we evaluated the association between EVT and 90-day functional outcome for men and women separately, adjusted for potential confounders. We tested for interaction between sex and EVT. Results—: We included 1762 patients in the analyses, of whom 833 (47%) were women. Women were older (median, 70 versus 66 years; P <0.001), were smoking less often (30% versus 44%; P <0.001), and had higher collateral grades (grade 3: 46% versus 35%; P <0.001) than men. Functional independence (modified Rankin Scale score, 0–2) at 90 days was reached by 318 women (39%) and 364 men (39%). The effect of EVT on the ordinal modified Rankin Scale was similar in women (adjusted common odds ratio [acOR], 2.13; 95% CI, 1.47–3.07) and men (acOR, 2.16; 95% CI, 1.59–2.96), with a P for interaction of 0.926. Conclusions—: Sex does not influence clinical outcome after EVT and does not modify treatment effect of EVT. Therefore, sex should not be a consideration in the selection of patients for EVT. Abstract : Supplemental Digital Content is available in the text.